Development of pluripotent stem cell‐based human tenocytes. (22nd December 2020) - Nakajima, Taiki; Ikeya, Makoto
Abstract: Human pluripotent stem cells (PSCs) are used as a platform for therapeutic purposes such as cell transplantation therapy and drug discovery. Another motivation for studying PSCs is to understand human embryogenesis and development. All cell types that make up the body tissues develop through defined trajectories during embryogenesis. For example, paraxial mesoderm is considered to differentiate into several cell types including skeletal muscle cells, chondrocytes, osteocytes, dermal fibroblasts, and tenocytes. Tenocytes are fibroblast cells that constitute the tendon. The step‐wise narrowing fate decisions of paraxial mesoderm in the embryo have been modeled in vitro using PSCs; however, deriving tenocytes from human‐induced PSCs and their application in cell therapy have long been challenging. PSC‐derived tenocytes can be used for a source of cell transplantation to treat a damaged or ruptured tendon due to injury, disorder, or aging. In this review, we discuss the latest research findings on the use of PSCs for studying the biology of tenocyte development and their application in therapeutic settings. Abstract : Deriving tenocytes from human‐induced PSCs and their application in cell therapy have long been challenging. In this review, we discuss the latest research findings on the use of PSCs for studying the biology of tenocyte development and their application in therapeutic settings.